The Relationship Between Prenatal Attachment and Social Support Levels of Pregnant Women in the Third Trimester and Factors Affecting this Relationship. - Aksoy, Ahu; Aksu, Aslıhan; Yılmaz, Duygu Vefikuluçay; Değirmenci, Filiz; Çelebi, Asiye (Journal of Education & Research in Nursing / Hemşirelikte Eğitim ve Araştırma Dergisi, 2021)
Background: This descriptive study was conducted to determine the relationship between prenatal attachment and perceived social support levels of pregnant women in the third trimester. Methods: The study sample consisted of 152 pregnant women who applied to the Non-Stress Test Outpatient Clinic of a public hospital between July 21 and September 22, 2017. Data were collected using a questionnaire form, the Multidimensional Scale of Perceived Social Support, and the Prenatal Attachment Inventory. Descriptive statistics from the data obtained were evaluated using Student's t-test for comparison of two group means and one-way analysis of variance for comparing more than two group means. Pearson correlation coefficient was used to determine the relationship between two continuous variables. Results: It was found that the mean score obtained by the pregnant women from the Social Support Scale was 57.93 ± 13.76 and the mean score from the Prenatal Attachment Inventory was 61.84 ± 10.07. Social support and prenatal attachment levels were greater in pregnant women with high school and higher levels of education. In addition, it was found that prenatal attachment levels were lower among pregnant women with a history of abortion and 3 or more pregnancies. There was a moderate positive correlation between the mean scores obtained from the Multidimensional Scale of Perceived Social Support and the Prenatal Attachment Inventory. Conclusion: It was determined that, as the perceived social support levels of pregnant women increased, their prenatal attachment levels also increased. In line with the results obtained from the study, it is recommended that nurses, who play a key role in increasing attachment in the prenatal period, should determine the sources and levels of social support for pregnant women and consider the relationship between social support and prenatal attachment with respect to the factors affecting this relationship.